ANALISIS FRAMING PEMBERITAAN MEDIA ONLINE DETIK.COM DAN KOMPAS.COM MENGENAI KEBIJAKAN KALTIM SILENT - Johantan Alfando Wikandana Sucipta; Rizky Chandra Kurniawan (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2021)
The country of Indonesia is currently faced with a big problem, namely Covid-19, which is currently increasingly troubling its citizens. This study discusses the analysis of media texts in the case of the program controversy set by the Governor of East Kalimantan Isran Noor